Pengaruh pengembangan sumber daya manusia dan kemampuan kerja terhadap kinerja karyawan PT. Jambi Media Grafika â€œTribun Jambiâ€ - Pramesrianto, Adela; Edward, Edward; Amin, Shofia (Jurnal Dinamika Manajemen, 2023)
The purpose of this study was to determine whether the development of human resources and work ability has an effect on employee performance. The data used in this study are primary data obtained through interviews, questionnaires and processed with the help of SPSS 22 and Windows 10. The population in this study were all employees at PT. Jambi Media Grafika or Tribun Jambi and the sample amounted to 60 people. Research from the hypothesis proves that work ability has a positive and significant effect on employee performance, but work ability has no and significant effect on employee performance. The implication of this research is that human resource development is very important in improving and enhancing employee performance in the company.